20th Biennial BDS Conference 2018. Issue 1 (13th February 2019) - Williamson, Tracey; Davies, Rachel
Abstract : This paper is an account of the 20th biennial BDS conference 2018. It describes the venue, attendance and programme and summarises the technical sessions and workshops.